Crisis Management in Tourism - Laws, Eric (CABI, 2014)
As the editors and contributors were working on this book, one of the most severe natural disasters in recorded history struck and devastated many places and communities around the Indian Ocean on 26 December 2004, after a suboceanic earthquake generated a vast tsunami. Only 3 years previously, the terrorist attack of 11 September 2001 (9/11) caused great damage, suffering and shock in the USA. Both of these events had significant consequences for the operation of tourism businesses. In both of these events, tourists and the tourism industry, although gravely affected, were not the most numerous nor the most seriously affected. In the concluding chapter, we discuss two further crises, the New Orleans hurricane and the strong possibility of a global bird flu pandemic, and draw lessons from them for the future management of tourism crises.